Pemberdayaan Umat sebagai Subjek Budaya - Khuza’i, Rodliyah (FIkom Unisba, 2005)
Postmodernism has penetrated human thinking in everywhere. As consequences, postmodernism affected interreligious relationship, intercultural connection, and civilization as well. There are at least three characters of postmodernism: deconstruction, pluralism, and relativism. This characters are functioned as methodology to comprehend religious in terms of postmodernism canons. By understanding religion using this methodology, religion is playing a role as filter of negative effect resulted from modernity and postmodern process. Religion also could be actively utilized to strengthen nation culture and religious life.